2016
DOI: 10.1111/beer.12122
|View full text |Cite
|
Sign up to set email alerts
|

Does gender influence managers’ ethics? A cross‐cultural analysis

Abstract: The relationship between gender and ethics has been extensively researched. However, previous studies have assumed that the gender-ethics association is constant; hence, scholars have seldom investigated factors potentially affecting the gender-ethics association. Thus, using managers as the research target, this study examined the relationship between gender and ethics and analyzed the moderating effect of cultural values on the gender-ethics association. The results showed that, compared with female managers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 81 publications
2
42
0
1
Order By: Relevance
“…The fact that gender did not have a significant influence on the likelihood of fraud in our regression models may seem counter‐intuitive because many studies have found that females tend to be more ethical than males (Chen, Tuliao, Cullen, & Chang, ). Indeed, based on a large‐scale survey of business managers in 27 nations, Chen et al () found that males were more likely to justify unethical business acts including tax evasion. Early studies of individual tax compliance generally supported the contention that females were more ethical, although by the mid‐1980s Jackson and Milliron () suggested that the gender gap was shrinking.…”
Section: Discussionmentioning
confidence: 76%
“…The fact that gender did not have a significant influence on the likelihood of fraud in our regression models may seem counter‐intuitive because many studies have found that females tend to be more ethical than males (Chen, Tuliao, Cullen, & Chang, ). Indeed, based on a large‐scale survey of business managers in 27 nations, Chen et al () found that males were more likely to justify unethical business acts including tax evasion. Early studies of individual tax compliance generally supported the contention that females were more ethical, although by the mid‐1980s Jackson and Milliron () suggested that the gender gap was shrinking.…”
Section: Discussionmentioning
confidence: 76%
“…Within the university specifically, gender is one of the most significant CG issues at a time of profound social change [29]. As to CSR and ethics, the presence of women on the board has a positive influence on ethical behavior of the organization [30], and striking differences emerge in the area of ethics when decisions are made by men vs. women [31]. Women and men perceive themselves facing differently from management in educational settings [28].…”
Section: Gender Of the University Rectormentioning
confidence: 99%
“…The social role theory argues that women possess characteristics related to a greater empathy with and concern for others (Eagly & Johannesen‐Schmidt, ); moreover, they are more communicative, democratic, participatory, and cooperative (Eagly, Johannesen‐Schmidt, & van Engen, ), they take greater account of the needs of stakeholders (Bear et al ., ), and they are less likely to justify business‐related unethical behavior than their male counterparts (Chen, Velasquez Tuliao, Cullen, & Chang, ). Accordingly, it is assumed that female directors are more likely to encourage the company to adopt a more socially responsible approach (Alonso‐Almeida, Casani Fernández de Navarrete, & Rodríguez‐Pomeda, 2015).…”
Section: Theoretical Background and Research Hypothesismentioning
confidence: 99%